DEVELOPMENT OF E-BOOK USING KVISOFT FLIPBOOK MAKER TO TRAIN SCIENCE PROCESS SKILL FOR SENIOR HIGH SCHOOL STUDENTS IN CURRICULUM 2013 - NINDY APSARI, ANGELA (Inovasi Pendidikan Fisika, 2017)
The aim of this study is to test feasibilitys e-book (validity, practicality, and effectiveness). E-book gets its feasibility if its value about  61% in good and excellent category. Research method is ADDIE (analyze, design, develop, implement, and evaluate). Collect the data by observing (practicality and effectiveness) and questioning (validity sheet and student response). The subjects are 28 students of 10 grades of Science (Muhamaddiyah 9 Senior High School Surabaya). Result of validity is fall into excellent category (91% of learning, 92% of material, and 87% of media). Result of practicality is is fall into good and excellent category (implementation 100%, constrain is no bother for this study). Result of effectiveness in attitude assessment is fall into good and excellent category (54% of curiosity,100 % of cooperate , 100% of honestly, 100% of responsible, and 50% of accuracy. Result of effectiveness in skill assessments is fall into good and excellent category (71% of observe, 82% of classify, 57% ask question, 100% of formulate the hypothesis, 100% of conduct the investigation, 89% of interpret, and 62% of communicate. Students response is excellent category. The result of this study is the development of eBook is success into its feasibility. Keywords: e-Book, Science Process Skill.